Inovasi Desain Tong Sampah Kreatif sebagai Strategi Peningkatan Kesadaran Masyarakat Terhadap Lingkungan di Desa Mekar Sawit - Ikhwana, Ikhwana (Journal of Community Sustainability, 2025)
This study focuses on the fact that Mekar Sawit Village has low awareness and behavior among residents regarding waste disposal and sorting, despite various policies and programs to manage waste. The lack of attractive facilities and active participation has led to the accumulation of waste and a decline in the aesthetics of the area. Therefore, innovative ideas are needed to change the perspectives and habits of residents.(1) Overall, the objective of this study is to evaluate the effectiveness of using creative trash can designs as a method to increase environmental awareness in Mekar Sawit Village. (2) Specifically, the objectives of this study are to examine (a) residents' knowledge and behavior regarding waste before the intervention, (b) create and implement creative trash bin prototypes that are appropriate for the local context, and (c) measure changes in awareness and waste disposal practices after the intervention.